Perilaku Kadarzi Ibu Balita Ditinjau dari Sudut Pengetahuan dan Prakteknya: Studi Kuantitatif di Suatu Wilayah Urban - Fatma Fatma; Yusran Nasution (MEDIA MEDIKA INDONESIANA, 2010)
The behavior of underfives mothers on kadarzi from their knowledge and practice: a quantitative study in an urban area Background: Poor families at urban area have a high risk to get undernutrition due to low purchasing power for buying nutritious foods. To overcome it, The Indonesian government have been declared Kadarzi (Nutrition Awareness Family) movement since 1998 which aimed to establish nutrition awareness family for achievement an optimal nutritional status of family. However, until now the behavior’s of underfives mothers on Kadarzi at Jakarta City almost unknown because of the limited study on Kadarzi. Actually, role of mothers in family is very important as primary target to determine nutritional status quality of their underfives. Objective: The study aimed to identify the behavior of underfives mothers on Kadarzi from knowledge and practice sites at Penjaringan Village, Penjaringan Sub-district, North Jakarta. Methods: The study design was cross sectional using structured interview to 105 of mothers aged 18-45 years who are still have underfives children. Results: The study revealed that the majority of mothers had low knowledge and practice of Kadarzi due to lack of socialization from local community health centers. They were unfamiliar with the terminology of Kadarzi and considered that Kadarzi was identical with the terms of four healthy and five perfect for toddlers and pregnant women to improve their nutrition and health status. Conclusion: Lack of knowledge and practice on Kadarzi had role on the poor of mothers’ behavior on Kadarzi. Key words: Kadarzi behavior, knowledge, practiceABSTRAKLatar belakang: Keluarga miskin di wilayah perkotaan adalah kelompok paling berisiko terpapar masalah gizi kurang akibat rendahnya daya beli makanan bergizi. Untuk mengatasinya, pemerintah telah meluncurkan Gerakan Kadarzi (Keluarga Sadar Gizi) sejak tahun 1998 dengan tujuan untuk mewujudkan keluarga mandiri sadar gizi guna mencapai status gizi keluarga yang optimal. Namun hingga sekarang, perilaku Kadarzi ibu balita di wilayah miskin (kumuh) di Kota Jakarta hampir tidak diketahui akibat terbatasnya studi. Padahal peran ibu dalam keluarga sangat penting sebagai sasaran primer dalam menentukan kualitas gizi balitanya. Studi ini dilaksanakan dengan tujuan untuk melakukan identifikasi perilaku Kadarzi dari sudut pengetahuan dan praktek ibu balita di Kelurahan Penjaringan, Kecamatan Penjaringan, Jakarta Utara. Metode: Desain studi adalah cross sectional dengan metode wawancara terstruktur pada 105 ibu usia 19-45 tahun yang masih memiliki anak balita. Hasil: Mayoritas ibu balita memiliki pengetahuan dan praktek Kadarzi yang rendah karena kurangnya sosialisasi dari puskesmas setempat. Mereka kurang mengenal istilah Kadarzi dan menganggapnya identik dengan terminologi empat sehat lima sempurna bagi anak balita dan ibu hamil untuk meningkatkan status gizi dan kesehatan. Simpulan: Rendahnya pengetahuan dan praktek ibu balita terhadap Kadarzi berperan terhadap minimnya perilaku Kadarzi ibu balita.